Analysing EEG alpha brainwave signal activities based on visual stimulation / Iza Sazanita Isa, Balkis Solehah Zainuddin, Zakaria Hussain and Nurul Huda Ishak - Isa, Iza Sazanita; Zainuddin, Balkis Solehah; Hussain, Zakaria (Faculty of Business Management, 2013)
A current conceptual studies and researches are focusing on rehabilitation of SCI (Spinal Cord Injury) and stroke sufferer by using FES (Functional Electrical Stimulation) induced. The amount of FES induced is depending on level of injury and the muscle since the electrical stimulate is only in μvolt. To have sufficient amount of FES stimulation, the brain signal that transmit to muscle movement is the main controller of the body. Therefore, this study is conducted to measure brainwave signal of alpha wave electrical activity and observed the effect on visual stimulation of alpha wave on healthy normal brain. The brainwave signals measured from scalp using surface electrodes and EEG (Electroencephalograph) to detect the brain activities based on visual stimulation. From the analyzing results, it indicates that alpha waves during periods of eyes closed are the strongest EEG brain signal. Alpha waves is the most suitable signals to be integrated for FES stimulation as it consistency in producing electrical brainwave signals The findings of this conceptual study can be recommended to be implemented to control amount of FES induced based on physical activities specifically for stroke rehabilitation therapy.